Low leptin concentration may identify heart failure patients with central sleep apnea - Cundrle, Ivan; Somers, Virend K; Singh, Prachi; Johnson, Bruce D; Scott, Christopher G; Olson, Lyle J (Journal of sleep research, 2018)
Low leptin concentration has been shown to be associated with central sleep apnea in heart failure patients. We hypothesized that low leptin concentration predicts central sleep apnea. Consecutive ambulatory New York Heart Association (NYHA) classes I-IV heart failure patients were studied prospectively, including measurement of serum leptin, echocardiography and polysomnography. Sleep apnea was defined by type (central/mixed/obstructive) and by apnea-hypopnea index ≥5 by polysomnography. Subjects were divided into four groups by polysomnography: (1) central sleep apnea, (2) mixed apnea, (3) no apnea and (4) obstructive sleep apnea. Fifty-six subjects were included. Eighteen subjects were diagnosed with central sleep apnea, 15 with mixed apnea, 12 with obstructive apnea and 11 with no sleep apnea. Leptin concentration was significantly lower in central sleep apnea compared to obstructive apnea (8 ± 10.7 ng mL-1 versus 19.7 ± 14.7 ng mL-1 , P ˂ 0.01) or no sleep apnea (8 ± 10.7 ng mL-1 versus 17.1 ± 8.4 ng mL-1 , P ˂ 0.01). Logistic regression showed leptin to be associated independently with central sleep apnea [odds ratio (OR): 0.19; 95% confidence interval (CI): 0.06-0.62; area under the curve (AUC): 0.80, P < 0.01]. For the detection of central sleep apnea, a cut-off value for leptin concentration 5 ng mL-1 yielded a sensitivity of 50% and specificity of 89%. In conclusion, a low leptin concentration may have utility for the screening of heart failure patients for central sleep apnea.
Keywords: leptin; Prospective Studies; polysomnografie; Humans; lidé středního věku; Sleep Apnea, Central; central sleep apnea; Middle Aged; prospektivní studie; heart failure; mužské pohlaví; Leptin; srdeční selhání; biologické markery; ženské pohlaví; Polysomnography; lidé; screening; Biomarkers; Aged; Heart Failure; senioři; spánková apnoe centrální; Male; Female